A Five-Year Review of Refractive Procedures, Outcomes and Complications - Robert Edward T. Ang, MD; Clarissa Marie S. Tady, MD; Niccolo Zandro R. Valencia, MD; Lilette Marie B. Canilao, MD; Dennis C. Vizconde, MD; Mark Christian R. Rivera, MD (Philippine Journal of Ophthalmology)
Objective: To evaluate the visual and refractive outcomes of LASIK, PRK, phakic IOL, and Supracor as treatment for errors of refraction, including presbyopia, performed at a private eye center.